Stress-level buffeting analysis of a long-span cable-stayed bridge with a twin-box deck under distributed wind loads. (15th November 2016) - Zhu, Q.; Xu, Y.L.; Shum, K.M.
Highlights: A framework for buffeting stress analysis using multi-scale bridge models with distributed wind loads. The chord-wise correlations of aerodynamic pressures on a twin-box deck have been examined. A new method to estimate distributed aeroelastic forces over a bridge deck section. Buffeting analyses using a multi-scale model yield larger maximum stress than a spine-beam model. Signature turbulence only affects the stress responses at low wind speeds. Abstract: To accurately predict buffeting-induced stresses in a long-span cable-stayed bridge with a twin-box deck, buffeting analyses should take into account the cross-sectional distribution of both aerodynamic and aeroelastic forces over the surface of the bridge deck. They should also be performed on an accurate multi-scale model rather than a spine-beam model of the bridge. This paper proposes a framework for stress-level buffeting analysis of a long-span cable-stayed bridge with a twin-box deck under distributed wind loads. Methods to obtain distributed aerodynamic and aeroelastic forces on the bridge deck are introduced. The proposed framework synthesizes the buffeting analysis with distributed wind loads and the multi-scale modelling and model updating of long-span bridges. The proposed framework is applied to the Stonecutters cable-stayed bridge in Hong Kong. The responses computed using the proposed buffeting analysis framework are compared with those computed using the sectional-force-based traditional method on a spine-beam model. The comparative results show significant differences in stress distribution on the twin-box deck and the multi-scale model yields larger maximum stress responses compared with the spine beam model.